Bilateral Cerebral Perfusion via Right Axillary Artery Cannulation Alone in Aortic Arch Surgery - Bassano, Carlo; Mvondo, Charles Mve; Bovio, Emanuele; Chiariello, Luigi (The Thoracic and Cardiovascular Surgeon, 2013)
Several methods have been proposed to avoid cerebral damage during aortic arch surgery. Antegrade, bilateral, selective cerebral perfusion is probably the most efficient one, although it has some drawbacks, such as air or particulate embolism risk, limitation in operative field visibility, and interactions with surgical maneuvers. We describe a surgical technique that provides bilateral antegrade perfusion to the brain, via the right axillary artery, with no need of additional arterial lines or shunting devices.
Keywords: aorta/aortic; cerebral protection